Comprehensive Characterization of the Attenuated Double Auxotroph Mycobacterium tuberculosisΔleuDΔpanCD as an Alternative to H37Rv - Mouton, Jomien M.; Heunis, Tiaan; Dippenaar, Anzaan; Gallant, James L.; Kleynhans, Léanie; Sampson, Samantha L. (Frontiers in Microbiology, 2019)
Currently available model organisms such as Mycobacterium smegmatis and Mycobacterium bovis Bacillus Calmette-Guérin (BCG) have significantly contributed to our understanding of tuberculosis (TB) biology, these models have limitations such as differences in genome size, growth rates and virulence. However, attenuated Mycobacterium tuberculosis strains may provide more representative, safer models to study M. tuberculosis biology. For example, the M. tuberculosis ΔleuDΔpanCD double auxotroph, has undergone rigorous in vitro and in vivo safety testing. Like other auxotrophic strains, this has subsequently been approved for use in biosafety level (BSL) 2 facilities. Auxotrophic strains have been assessed as models for drug-resistant M. tuberculosis and for studying latent TB. These offer the potential as safe and useful models, but it is important to understand how well these recapitulate salient features of non-attenuated M. tuberculosis. We therefore performed a comprehensive comparison of M. tuberculosis H37Rv and M. tuberculosis ΔleuDΔpanCD. These strains demonstrated similar in vitro and intra-macrophage replication rates, similar responses to anti-TB agents and whole genome sequence conservation. Shotgun proteomics analysis suggested that M. tuberculosis ΔleuDΔpanCD has a heightened stress response that leads to reduced bacterial replication during exposure to acid stress, which has been verified using a dual-fluorescent replication reporter assay. Importantly, infection of human peripheral blood mononuclear cells with the 2 strains elicited comparable cytokine production, demonstrating the suitability of M. tuberculosis ΔleuDΔpanCD for immunological assays. We provide comprehensive evidence to support the judicious use of M. tuberculosis ΔleuDΔpanCD as a safe and suitable model organism for M. tuberculosis research, without the need for a BSL3 facility.